Analysis of Prospective Mathematics Teachers’ Critical Thinking Disposition Based on Self-Confidence - Basri, Hasan; Tonra, Wilda Syam; Yahya, Farida Hanim; Darmawan, Puguh; Kurniati, Dian; Indahwati, Rohmah; Saleh, Sitti Fithriani (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
The disposition of critical thinking plays an important role for teachers, particularly in responding to mathematical problems. However, several studies have shown that the disposition to think critically is still low. This descriptive-qualitative research aims to analyze and describe prospective mathematics teachers’ critical thinking dispositions based on their self-confidence. Three subjects were selected from a total of 25 prospective mathematics teachers who were given a self-confidence questionnaire, with very good, good, and poor self-confidence criteria. Data collection was conducted by administering a critical thinking disposition test of the Problems With No Specified Universal Set Given (PWNSUS) type and conducting interviews. The results of this research indicate that prospective mathematics teachers’ self-confidence influences their critical thinking disposition. Prospective mathematics teachers with very good self-confidence fulfill the components of a critical thinking disposition, namely systematicity, self-confidence, inquisitiveness, open-mindedness, and analyticity. Meanwhile, prospective mathematics teachers with good self-confidence fulfill the components of self-confidence, inquisitiveness, open-mindedness, and analyticity. However, prospective mathematics teachers with poor self-confidence only fulfill inquisitiveness and analyticity. Two of the three subjects were unable to achieve two critical thinking components, namely truth and maturity, which can be developed through various exercises.